2017
DOI: 10.1016/j.orggeochem.2016.11.002
|View full text |Cite|
|
Sign up to set email alerts
|

Branched GDGT signals in fluvial sediments of the Danube River basin: Method comparison and longitudinal evolution

Abstract: Abundances and distributional changes of branched glycerol dialkyl glycerol tetraethers (brGDGTs) in fluvially influenced sediments are used in various paleoclimate studies to reconstruct variations in soil export, continental air temperature and soil pH in corresponding river basins. For accurate interpretation of these records, it is important to understand the provenance and the evolution of biomarker signals as they move through the river system. Here we investigate the brGDGT composition of modern river s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
55
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 32 publications
(57 citation statements)
references
References 47 publications
2
55
0
Order By: Relevance
“…brGDGTs: The preparation of a brGDGT fraction from the neutral phase and its subsequent measurement is described in Freymond et al (2017). The brGDGT concentration data reported here were acquired with the 'classic' method, i.e.…”
Section: Lipid Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…brGDGTs: The preparation of a brGDGT fraction from the neutral phase and its subsequent measurement is described in Freymond et al (2017). The brGDGT concentration data reported here were acquired with the 'classic' method, i.e.…”
Section: Lipid Analysismentioning
confidence: 99%
“…The brGDGT concentration data reported here were acquired with the 'classic' method, i.e. without the separation of 5-methyl and 6methyl brGDGT isomers, using an HPLC-APCI-MS equipped with a Grace Prevail cyano column (150 mm  2.1 mm, 3 mm) (Schouten et al, 2007;Freymond et al, 2017). This form of data is presented so that all available Danube catchment data, including samples that were not measured with the 'improved chromatography' method, could be used.…”
Section: Lipid Analysismentioning
confidence: 99%
“…The brGDGTs in the marine sediments were first assumed to represent an integrated signal of the entire river basin from where the soil brGDGTs derive (Weijers et al, 2007a). However, it has been shown that the reconstructed MAT and soil pH can be biased toward a certain area and/or period of increased input of brGDGTs to the river (Freymond et al, 2017). In addition, the hydrodynamics and microbial activity during fluvial transport might influence the distribution of brGDGTs along the river (Zell et al, 2013a(Zell et al, ,b, 2014aDe Jonge et al, 2014b, 2016, and the marine in situ production of brGDGTs may affect the original signal of the soil-derived material (Peterse et al, 2009;Zhu et al, 2011;Hu et al, 2012;Liu et al, 2014;Zell et al, 2014a,b;Sinninghe Damsté, 2016).…”
Section: Implications For Soil Ph and Continental Mat Reconstructionsmentioning
confidence: 99%
“…There were 46 riverbed sediments (main river and tributaries, Fig. 2a) collected as described by Freymond et al (2018) in spring 2013 and 2014. The riverbed sediments were wet sieved with Milli-Q water over a 63 µm sieve on a (Usman et al, 2018) with enhanced view of the delta region, (b) concentrations of LCDs in SPM (collected during wet and dry seasons), and (c) concentrations of LCDs in sediments (collected during wet and dry seasons).…”
Section: Danube and Black Seamentioning
confidence: 99%
“…The extracts were dried under N 2 and an 80 % aliquot was further processed for analysis. The samples from the Danube were extracted as described by Freymond et al (2018) using microwave extraction (MARS) with 9 : 1 DCM : MeOH (v/v, 25 min at 100 • C). The Meteor-Poseidon Black Sea surface sediments were extracted three times ultrasonically with a 9 : 1 DCM : MeOH (v/v) solvent mixture after addition of 1.96 µg of C 22 7,16-diol as the internal standard.…”
Section: Lipid Extractionmentioning
confidence: 99%